Breaking the Limit of Micro‐Ductility in Oxide Glasses. Issue 18 (24th July 2019) - Januchta, Kacper; Stepniewska, Malwina; Jensen, Lars R.; Zhang, Yang; Somers, Marcel A. J.; Bauchy, Mathieu; Yue, Yuanzheng; Smedskjaer, Morten M.
Abstract: Oxide glasses are one of the most important engineering and functional material families owing to their unique features, such as tailorable physical properties. However, at the same time intrinsic brittleness has been their main drawback, which severely restricts many applications. Despite much progress, a breakthrough in developing ultra‐damage‐resistant and ductile oxide glasses still needs to be made. Here, a critical advancement toward such oxide glasses is presented. In detail, a bulk oxide glass with a record‐high crack resistance is obtained by subjecting a caesium aluminoborate glass to surface aging under humid conditions, enabling it to sustain sharp contact deformations under loads of ≈500 N without forming any strength‐limiting cracks. This ultra‐high crack resistance exceeds that of the annealed oxide glasses by more than one order of magnitude, making this glass micro‐ductile. In addition, a remarkable indentation behavior, i.e., a time‐dependent shrinkage of the indent cavity, is demonstrated. Based on structural analyses, a molecular‐scale deformation model to account for both the ultra‐high crack resistance and the time‐dependent shrinkage in the studied glass is proposed. Abstract : Rational composition design makes it possible to break the limit of micro‐ductility in oxide glasses . When subjected to surface aging, the designed caesium aluminoborate glass displays superior resistance against sharp contact loading compared to all other oxide glasses, surpassing them by an order of magnitude. The structural origin of such micro‐ductility is ascribed to an observed stress‐assisted surface hydrolysis.